2016
DOI: 10.3402/jev.v5.32945
|View full text |Cite
|
Sign up to set email alerts
|

Techniques used for the isolation and characterization of extracellular vesicles: results of a worldwide survey

Abstract: Extracellular vesicles (EVs) represent an important mode of intercellular communication. Research in this field has grown rapidly in the last few years, and there is a plethora of techniques for the isolation and characterization of EVs, many of which are poorly standardized. EVs are heterogeneous in size, origin and molecular constituents, with considerable overlap in size and phenotype between different populations of EVs. Little is known about current practices for the isolation, purification and characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
711
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 798 publications
(771 citation statements)
references
References 22 publications
13
711
0
9
Order By: Relevance
“…These three characteristics support the claim that the 150k pellet contains EVs [11,24]. It is widely accepted that the differential ultracentrifugation protocol, used in our study and by most EVs research groups [2628], does not allow optimal separation of exosomes and MVs. Indeed, small-sized MVs are likely present in the 150k pellet [29,30].…”
Section: Discussionsupporting
confidence: 85%
“…These three characteristics support the claim that the 150k pellet contains EVs [11,24]. It is widely accepted that the differential ultracentrifugation protocol, used in our study and by most EVs research groups [2628], does not allow optimal separation of exosomes and MVs. Indeed, small-sized MVs are likely present in the 150k pellet [29,30].…”
Section: Discussionsupporting
confidence: 85%
“…Rapidly increasing research in this field is accompanied by the demand for reproducible, time-efficient and economic isolation methods. A recent survey conducted by Gardiner et al revealed that although ultracentrifugation (UC) remains the most commonly used isolation method, other approaches have gained preference when starting volume is limited [1]. Capturing EVs from blood-based biofluids such as serum and plasma is of particular interest for clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been used for EV isolation, but each method has its advantages and disadvantages. We have tested DUC, the most commonly used isolation technique [18], as it is a simple approach and has a rather high throughput. Furthermore, it has the advantage that EVs are concentrated in a pellet suitable for undiluted resuspension in SPP for further coagulation analysis.…”
Section: Discussionmentioning
confidence: 99%